Prevalence of environmental Burkholderiapseudomallei in Sri Lanka - K. Assig; E. Corea; B. Folli; M. Abeykoon; N. Mubarak; T. Kumanan; T. Senanayake; B. Piyasiri; I. Steinmetz (Sri Lankan Journal of Infectious Diseases, 2017)
No abstract available